Schizencephaly – A case report - Chhetri, PK; Raut, S (Journal of College of Medical Sciences-Nepal, 2010)
Schizencephaly is an uncommon congenital cerebral malformation that involves the cerebral mantle and consists of a cleft that extends through the entire cerebral hemisphere from the lateral ventricle to cerebral cortex. The condition is present at birth and present early in life. Here we present an adult patient with schizencephaly presenting with first onset seizure. Key words: schizencephaly; lateral ventricle; seizure imaging diagnosis DOI: 10.3126/jcmsn.v6i1.3604 Journal of College of Medical Sciences-Nepal, 2010, Vol. 6, No. 1, 54-56